Impact of left ventricular function on clinical outcomes of functional mitral regurgitation patients undergoing transcatheter mitral valve repair. Issue 7 (19th February 2016) - Azzalini, Lorenzo; Millán, Xavier; Khan, Razi; Couture, Philippe; Ducharme, Anique; Basmadjian, Arsène; Bonan, Raoul; Asgar, Anita W.
Abstract : Objectives: To evaluate the impact of baseline left ventricular (LV) function on the clinical outcomes of patients with functional mitral regurgitation (FMR) treated with MitraClip. Background: It is unknown whether patients with significant FMR and severe LV dysfunction benefit from MitraClip. Methods: A cohort of 77 patients with significant FMR undergoing MitraClip procedure between December 2010 and January 2015 was categorized by baseline LV ejection fraction (LVEF) into tertiles: LVEF <27% ( n  = 27), LVEF 27–37% ( n  = 25), and LVEF >37% ( n  = 25). We sought to evaluate the impact of LVEF on all‐cause mortality at follow‐up. Results: There were no significant differences in baseline comorbidities, medical treatment and MR severity among tertiles of LVEF. Overall procedural success was 94%, with no differences among groups (LVEF <27%: 89%; LVEF 27–37%: 100%; LVEF >37%: 92%; P  = 0.25). Median follow‐up was 372 days (interquartile range: 128–627 days). MR severity improved in all three groups, as compared to baseline. There were no differences in the prevalence of MR ≤2+ on follow‐up ( P  = 0.40). Mortality was highest in patients with LVEF <27% (41%), as compared with LVEF 27–37% (16%) and LVEF >37% (4%), P  = 0.004. Patient who died had a lower baseline LVEF compared to those who survived (24.8 ± 7.7% versus 35.5 ± 13.7%, P  < 0.001). An LVEF <27% was an independent predictor of mortality after adjusting for procedural success: hazard ratio 3.4 (95% CI: 1.1 to 10.0; P  = 0.030). Conclusions: MitraClip is effective in FMR patients regardless of the severity of LV dysfunction. However, low baseline LVEF is associated with increased mortality, despite procedural success. © 2016 Wiley Periodicals, Inc.